Bioprospecting of Palmyra Palm (Borassus flabellifer) Nectar: Unveiling the Probiotic and Therapeutic Potential of the Traditional Rural Drink - Pammi, Nagamani; Bhukya, Kiran Kumar; Lunavath, Ravi Kumar; Bhukya, Bhima (Frontiers in Microbiology, 2021)
The present study investigates the therapeutic and probiotic attributes of traditional Toddy Palm Nectar (TPN). Glucose was found to be the highest with 4.37 mg/ml and arabinose was the least with 2.85 mg/ml. The average ethanol concentration of fresh TPN was found to be 0.3 mg/ml. The nutritional profile of TPN revealed 18 volatile fatty acids, the major one being hexadecenoic acid (M/Z 74). Amino acid profiling showed 26 amino acids, with OH-lysine-2 the highest (12.86%). About 120 morphologically distinct lactic acid bacteria (LAB) were isolated from 26 TPN samples, based on differential growth and in vitro probiotic characteristics. After 16S rRNA sequencing, four indigenous LAB strains were identified as Lactobacillus plantarum group OUBN1, Enterococcus faecium OUBN3, Pediococcus acidilactici OUBN4, and Pediococcus pentosaceous OUBN5, and their sequences were deposited to NCBI. Safety evaluation studies showed the absence of haemolytic, gelatinolytic and proteolytic activity. The bacterial isolate OUBN3 showed a maximum survival rate of 6.91±0.04 log cfu/ml at acidic pH 2.5 and isolate OUBN5 showed 6.94 ± 0.02 log cfu/ml at pH 3.0. Similarly, the isolate OUBN5 showed 7.92 ± 0.03 log cfu/ml to 0.3% ox-bile after 4 h and 8.94 ± 0.03 log cfu/ml to simulated gastric juice after 3 h of treatments. OUBN1 expressed the highest autoaggregation (81.76 ± 1.25%), cell surface hydrophobicity (79.71 ± 3.42%), and displayed the maximum coaggregation with E. coli MTCC452 (76.96%), K. pneumoniae MTCC109 (75.62%), and S. aureus MTCC902 (70.69%). All strains showed significant antibiotic and antimicrobial activity. Isolate OUBN1 displayed hydroxyl radical scavenging activity (68.71 ± 1.0 %) with an IC50 value of 75.62 µg/ml and the highest anti-cancer activity (percentage inhibition of 88.55) against HT-29 cells. Based on the characteristics observed, L. plantarum group OUBN1 and P. pentosaceous OUBN5 were found to be potential isolates to employ as probiotic microbiota in food and forage preparations. These findings reinforce the fact that LAB isolated from TPN could be exploited as an alternative means towards potential therapeutic applications.